2009
DOI: 10.1007/s11356-009-0274-6
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of trace elements in blood and feed of homebred animals in Southern Serbia

Abstract: The presented study is a part of the long term ongoing project on the health risk assessment on animals and humans in the region. The collected data is intended to provide a base for the animal and human risk assessment as well as an estimate of the general pollution status of the environment in the region. Since some of the investigated elements are classified as important trace elements for livestock, the results could also be used to balance and improve the animal diet and thus, improve the growth and repro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 41 publications
4
23
0
Order By: Relevance
“…After pork breast is added, the other added ingredients are prepared lentil flour and sodium water with nitrite. The temperature of the prepared minced meat is monitored not to exceed [8][9][10] o С for the stirring time of 6 minutes. The prepared minced meat is used to stuff natural casings by using a vacuum syringe.…”
Section: Materials and Methods For Studying Toxic Elements And Radionmentioning
confidence: 99%
See 1 more Smart Citation
“…After pork breast is added, the other added ingredients are prepared lentil flour and sodium water with nitrite. The temperature of the prepared minced meat is monitored not to exceed [8][9][10] o С for the stirring time of 6 minutes. The prepared minced meat is used to stuff natural casings by using a vacuum syringe.…”
Section: Materials and Methods For Studying Toxic Elements And Radionmentioning
confidence: 99%
“…Concentrations of elements of aluminum, arsenic, cadmium, chromium, cobalt, copper, lead, mercury, nickel, selenium, and zinc penetrate into meat with contaminated air and vegetation [8]. In particular, according to the results of researching meat of wild and livestock [9] animals, it has been established that the presence of these elements does not present any danger to the health of consumers as their number does not exceed the maximum permissible concentrations [10].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…A great number of scientists explore the issues of nanocitrates, comparing toxicity of analogues [7][8][9][10][11][12].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Concentrations of elements of aluminum, arsenic, cadmium, chromium, cobalt, copper, lead, mercury, nickel, selenium and zinc get into meat during air and vegetation contamination [12]. In particular, according to results of examination of meat of wild and domestic animals [13], it was found that the existence of these elements does not pose any danger to the health of consumers, their amount does not exceed maximum permissible concentrations [14].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The territory of Yugoslavia was contaminated with 3.8×10 15 Bq of 137 Cs. The contamination was very inhomogeneous, and the highest/lowest level of contamination ratio was 83 (Popović et al 2009). This inhomogeneous distribution was due to the general meteorological conditions, rainfall as well as wind directions.…”
Section: Introductionmentioning
confidence: 98%